Adaptability, socialization and resilience: towards a new concept of library - Dantas, Taisa; de Sousa Guerreiro, João; Cordón-García, José Antonio (Revista General de Información y Documentación, 2017)
Currently, libraries face many challenges, but also new opportunities. The recent panorama of books and information requires libraries to take new actions designed to give new answers adapted to the current citizens’ needs. This exploratory study presents a trend map for the librarian sector applicable to different scenarios regardless of the target (university, public or school), its dimension or the environment in which it works (digital or physical), depending on the needs of each community. The main contribution of this study is to confirm that libraries remain as a place with a great social importance and demonstrated that through open spaces and multidisciplinary activities there is a flexibility to adapt depending of the needs, tastes or interests of the citizens.
Keywords: Libraries; digital reading; digital libraries; citizenship participation; lifelong learning